2018
DOI: 10.1111/joor.12722
|View full text |Cite
|
Sign up to set email alerts
|

The mediator effect of cognition on the relationship between brain lesion location and dysphagia in patients with stroke: Applying a structural equation model

Abstract: Summary Background Cognitive status is important for performing the assessment and treatment of dysphagia. Nonetheless, the cognitive neuropsychological profile of patients with stroke and dysphagia is not studied as deeply enough as it should be. On the one hand, focal and non‐focal brain lesions may lead to dysphagia and cognitive disorders, and on the other hand, the cognitive status possibly affects swallowing. In this study, cognition is supposed to be a mediator between brain lesion and swallowing disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 33 publications
1
15
1
Order By: Relevance
“…The high incidence of silent aspiration may be due to poor sensation, which can be suspected in many patients. Impaired cognition and awareness were common in these patients and probably had an impact on swallowing function, as seen in previous studies [ 32 , 33 ].…”
Section: Discussionsupporting
confidence: 70%
“…The high incidence of silent aspiration may be due to poor sensation, which can be suspected in many patients. Impaired cognition and awareness were common in these patients and probably had an impact on swallowing function, as seen in previous studies [ 32 , 33 ].…”
Section: Discussionsupporting
confidence: 70%
“…With regard to disease phase, three articles reported an association between swallowing disorders and the acute phase 6,19,22 . Meta‐analysis of this relationship yielded an OR of 3.23 and 95%CI of 2.33–4.48, indicating a significant association.…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies used the Mini‐Mental Status Examination (MMSE) to assess cognitive disorder, 7,10,16–22 and one study used the Montreal Cognitive Assessment 6 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, Ebrahimian et al found that cognitive deficits played a role in dysphagia occurrence after stroke. Considering the varying nature of swallowing problems in patients with cognitive disorders and stroke-induced dysphagia (6), the symptoms of dysphagia may encompass irregular meal times to progressive weight loss. On the other hand, in primary dysphagia, symptoms include longer feeding periods, multiple swallows, smaller bites, and prolonged chewing (7).…”
Section: Introductionmentioning
confidence: 99%